2009
DOI: 10.1021/jp904198d
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Faces of Cu2O and Their Stabilities in Photocatalytic Reactions

Abstract: Cu 2 O microcrystals with well-formed facets were synthesized by a simple hydrothermal method. The surface stabilities and photocatalytic properties of Cu 2 O microcrystals were systematically investigated. Cu 2 O {100} and {110} facets gradually disappear and transform into nanosheets during the photodegradation of methyl orange (MO) dye. With the increase of irradiation time, Cu 2 O microcrystals completely transform into nanosheets with {111} facets. The finally formed nanosheets exhibit stable photocatalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
269
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 374 publications
(284 citation statements)
references
References 41 publications
12
269
2
1
Order By: Relevance
“…The synthesis of Cu 2 O micro or nanostructures with controllable morphologies has been developed [14,15], including nanocubes [15,16], octahedra [15,16], polyhedral morphology [17], hollow structures [18] and nanowires [19], and many growth mechanisms have been proposed. These Cu 2 O microcrystals were generally synthesized by hydrothermal methods in the presence of different capping reagents (e.g., surfactant [20], ascorbic acid or hydrazine hydrate [16], and acetic acid [17]). The photodegradation of organic pollutants in a suspended catalyst system would cause several problems, such as difficulty in the recovery of photocatalysts, easy agglomeration and decreased active surface, low efficiency and the risk of secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of Cu 2 O micro or nanostructures with controllable morphologies has been developed [14,15], including nanocubes [15,16], octahedra [15,16], polyhedral morphology [17], hollow structures [18] and nanowires [19], and many growth mechanisms have been proposed. These Cu 2 O microcrystals were generally synthesized by hydrothermal methods in the presence of different capping reagents (e.g., surfactant [20], ascorbic acid or hydrazine hydrate [16], and acetic acid [17]). The photodegradation of organic pollutants in a suspended catalyst system would cause several problems, such as difficulty in the recovery of photocatalysts, easy agglomeration and decreased active surface, low efficiency and the risk of secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various semiconductor metal oxides as photocatalyst, Cu 2 O NPs find a special place in photocatalysis under visible light [10][11][12][14][15][16]. Wide applications of this oxide NPs are mainly owing to its nontoxicity, easy availability of cheap and up-scalable synthetic routes, lying of the band gap (i.e., 2.17 eV) in the visible range, tunability of band gap, and strong tendency to adsorb molecular oxygen which helps in scavenging the photogenerated electrons so that electron-hole pairs recombination can be restrained easily at the interface [10][11][12][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Wide applications of this oxide NPs are mainly owing to its nontoxicity, easy availability of cheap and up-scalable synthetic routes, lying of the band gap (i.e., 2.17 eV) in the visible range, tunability of band gap, and strong tendency to adsorb molecular oxygen which helps in scavenging the photogenerated electrons so that electron-hole pairs recombination can be restrained easily at the interface [10][11][12][14][15][16]. It is reported that size and shape are of paramount importance in tailoring the various properties and applications of the Cu 2 O NPs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations